Physical and physiological attributes of coffee seeds (Coffea arabica L) - Vidal-Tejeda, Claudia Andrea (2023)
Coffee is one of the most consumed and traded beverages worldwide and also the source of livelihood for millions of people. Knowledge of physical characteristics is essential for the design and manufacture of equipment for processing of coffee beans. This work was carried out in the seed laboratory of the Universidad National Agraria La Molina using 12 accessions of Coffea arabica. In each genetic material, physical and physiological characteristics were quantified such as polar and equatorial diameter, and thickness, as well as arithmetic diameter, geometric diameter, degree of sphericity, surface area, volume and percentage of germination/volume and germination percentage. The results indicated that UNACAF-172 and UNACAF-146 showed greater polar, arithmetic and geometric diameter. In addition, they showed greater surface area, volume and seedling weight. On the contrary, these same accessions had a lower germination percentage. Similarly, UNACAF-119 and UNACAF-90 showed low physical attributes, although high germination percentage and low seedling weight. In conclusion, the genetic component plays an important role in the physical and physiological attributes of coffee seeds.